1988
DOI: 10.1104/pp.86.4.1276
|View full text |Cite
|
Sign up to set email alerts
|

Calcium in the Regulation of Gravitropism by Light

Abstract: The red light requirement for positive gravitropism in roots of corn (Zea mays. cv "Merit") provides an entry for examining the participation of calcium in gravitropism. Applcations of calcium chelators inhibit the light response. Calcium channel blockers (verapamil, lanthanum) can also inhibit the light response, and a calcium ionophore, A23187, can substitute for light. One can substitute for red light by treatments which have elsewhere been shown to trigger Ca2l influx into the cytosol, e.g. heat or cold sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…The curvature of light-exposed roots was 46.2 ± 1.9° (Table IV). ABA also substituted partially for the light effect and enhanced the Ca2+-stimulated curvature of Alaska pea roots in the dark (Table V) Elevation of cytoplasmic Ca2" levels in the root cap, previously proposed to play an important role in signal transduction of gravity (2,19,23,25), could participate in gravitropic curvature of roots through its stimulatory action because many studies have shown that an acceleration of root elongation takes place following gravistimulation (13,14,26). In this regard, root curvature away from a Ca2" source appears to be the opposite of reports that there is a Ca2' redistribution with more accumulation on the bottom side of the graviresponding roots curving down (18,21 Differences in responsiveness of roots to Ca2" may also result from different water conditions at the tip as described in "Materials and Methods" (20,29).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The curvature of light-exposed roots was 46.2 ± 1.9° (Table IV). ABA also substituted partially for the light effect and enhanced the Ca2+-stimulated curvature of Alaska pea roots in the dark (Table V) Elevation of cytoplasmic Ca2" levels in the root cap, previously proposed to play an important role in signal transduction of gravity (2,19,23,25), could participate in gravitropic curvature of roots through its stimulatory action because many studies have shown that an acceleration of root elongation takes place following gravistimulation (13,14,26). In this regard, root curvature away from a Ca2" source appears to be the opposite of reports that there is a Ca2' redistribution with more accumulation on the bottom side of the graviresponding roots curving down (18,21 Differences in responsiveness of roots to Ca2" may also result from different water conditions at the tip as described in "Materials and Methods" (20,29).…”
Section: Resultsmentioning
confidence: 99%
“…The light effect on gravitropism of light-requiring orthogravitropic roots is considered to be mediated by phytochrome in the root cap (8), and agents such as the Ca2+ ionophore, A23187 (23,25), and ABA (19) (Table IV). Ca2+-stimulated curvature of pretreated roots was 33.2 ± 1.8°in 4 h, whereas roots without pretreatment showed no curvature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…plastic box that was closed to maintain an environment of high humidity (8). Prior to treatment, the box was equilibrated at least 1 h in the dark with the roots at 1800 orientation from the upright vertical.…”
Section: Methodsmentioning
confidence: 99%
“…In the roots of corn seedlings, the sensing step has been identified most readily with the sedimentation of amyloplasts in the root cap. The transduction step for orthogravitropism can be linked to a phytochrome stimulus (4) and a disturbance in cytoplasmic calcium concentrations (5,9,10,12,13,15). The motor step has been assumed to involve a hormonal redistribution-most likely of auxin or ABA (cf.…”
mentioning
confidence: 99%